MODERN METHODS OF TEACHING ENGLISH IN HIGHER EDUCATION - Tojiboyeva Mohinur Sherali qizi; Abduqodirov Umidjon Nazirovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article describes various methods of teaching foreign languages in universities. Particular attention was paid to the following methods: the direct method, grammar-translation, audio-visual, audiolingual and communicative. It is concluded that communicative method has started becoming the most widely-used.